'A FRIEND TO RATIONAL PIETY': THE EARLY RECEPTION OF HERDER BY PROTESTANT DISSENTERS IN BRITAIN. (January 2016) - Angerson, Catherine
ABSTRACT: Johann Gottfried Herder (1744–1803) already had an attentive British readership in 1800, when the first translation of his Ideen zur Philosophie der Geschichte der Menschheit (1784–91) was published in London. This curious episode in Anglo‐German literary relations and the reasons why there was a market for this German philosophical book at the turn of the nineteenth century have not been analysed in detail before. The article examines how Herder was first received in Britain as an intellectual ally of liberal Presbyterians and 'rational' Dissenters and later attacked and rejected on political grounds by the conservative Anglican establishment. An overview of the earliest reviews of Herder's Abhandlung über den Ursprung der Sprache (1772) in the Monthly Review in 1775 and 1784 is followed by an analysis of how Herder's theology, Biblical studies and philosophy of history were first received in journal reviews, usually in small fragments and often prior to the availability of English translations. By the time Thomas Churchill's translation of the Ideen appeared in 1800, Herder and some of his ideas were already the subject of intense discussion in intellectual Presbyterian and Unitarian circles in the politically heated aftermath of the French Revolution. Ein Kuriosum der englisch‐deutschen Literaturbeziehungen ist, dass Johann Gottfried Herder (1744–1803) schon um 1800 – als die erste englische Übersetzung seiner Ideen zur Philosophie der Geschichte der Menschheit (1784–91) in London erschien – eine sehr aufmerksame englische Leserschaft hatte. Die spezifischen Gründe, weshalb es einen Markt für diese deutsche philosophische Abhandlung gab, wurden noch nicht hinreichend analysiert. Der Aufsatz untersucht, wie Herder erst als intellektueller Verbündeter liberaler Presbyterianer und 'rationaler' Nonkonformisten positiv aufgenommen und später vom entgegengesetzten Lager des konservativen, anglikanischen Establishments politisch abgelehnt und heftig bekämpft wurde. Nach einem Überblick über die von der Forschung vernachlässigten frühesten Rezensionen von der Abhandlung über den Ursprung der Sprache (1772) im Monthly Review (1775 und 1784) wird die Rezeption von Herders Theologie, Bibelauslegung und Philosophie der Geschichte in den 1790er Jahren in Zeitschriftenartikeln analysiert: gewöhnlich handelte es sich um kleine Fragmente, die oft vor den englischen Übersetzungen erschienen. Herder und einige seiner Ideen waren schon vor der Erscheinung von Thomas Churchills Übersetzung der Ideen in intellektuellen presbyterianischen und unitarischen Kreisen in der aufgeheizten politischen Atmosphäre nach der Französischen Revolution Gegenstand heftiger Diskussionen.